The lady in the car with glasses and a gun [videorecording (DVD)] - Mavor, Freya; Biolay, Benjamin, 1973-; Germano, Elio; Martin, Stacy, 1991-; Japrisot, Sébastien, 1931-2003 (Magnolia Home Entertainment, 2016)
Secretary takes her boss's car for getaway holiday in the Mediterranean, on the trip, she is recognized by people she has not met before. When a body turns up in her trunk, things get serious as she implicated in a crime she knows nothing about. She must now figure out about to prove she is innocent.